PENGARUH MOTIVASI DAN DISIPLIN SERTA LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI SEKRETARIAT DAERAH KABUPATEN OGAN KOMERING ILIR - Atmawijaya, Ganda (Universitas muhammadiyah palembang, 2012)
The purpose of this research is to know the influence of motivation, discipline, and workeEnvironment not only jointly but also partially of employee performance for Secretariat of Ogan Komering Ilir Area. This research used 63 employees for the samples. Analysis which used is multiple linier regression analysis. To know the influence of motivation, discipline, and work environment jointly used F test and partially used t test From the calculation, F-arithmetic (33,764) and P value is 0,000. Another calculation is F-table (2,761) and P value is 0,000, and alpha which used is (0,05). From the description above, we know that motivation, discipline and work environment had influence for employee performance if we used partially that have T-arithmetic for motivation variable (43,2555) and P value (0,014), discipline variable (5,954) with P value (0,000), and T-arithmetic work environment (2,867) with P value (0,035). It has different with T-table (1,999) with jointly that have influence of motivation, discipline, and work environment of employee performance